Modeling of two dimensional array based overlay network for live video streaming - Ibrahimy, Abdullah Faruq (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
A two dimensional array-based overlay network is proposed to stream the live video data. Instead of streaming in conventional tree-based or in mesh-based overlay network, the overlay network efficiently utilizes the additional upload bandwidth of peers to minimize live video data delivery delay. In the proposed network, there is always a peer or a live video streaming server available to upload the live video stream data, so the overlay network is very stable. Placement of peers in the two dimensional array enhances the scalability of the overlay network. Peers are placed in a two dimensional array and higher strength peers are placed closer to the live video streaming server. Strength of peers is determined according to their upload and download bandwidth, which enhances the balance of load and performance. The approaches, which are used for distributing the additional upload bandwidth of the peers, distributes the additional upload bandwidth to the heterogeneous strength peers in a fair treat distribution approach and to the homogeneous strength peers in a uniform distribution approach. Packets are diffused to the heterogeneous strength peers by preferring the higher strength peer and to the homogeneous strength peers by preferring the peer with lowest delay. The performance has been analyzed by simulating the overlay network with QualNet from Scalable Network Technologies. Compared to Fast Mesh, the maximum delay and the average delay have significantly decreased. The maximum delay and average delay increments are not very high for the increment of every 100 peers from 100 peers to 1000 peers. So the overlay network can be considered as a scalable overlay network. The jitter or delay variation is within the limit of acceptable range of jitter or delay variation of live video streaming. The maximum and average hop counts are also lower compared to the Fast Mesh overlay network.